Kekuatan Hukum Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 tentang Petunjuk Bagi Hakim dalam Mengadili Perkara Permohonan Pencatatan Perkawinan Antar-Umat yang Berbeda Agama dan Kepercayaan - Muharrir, Muharrir; Maulana, Jefrie; Zulfikar, Muhammad Nahyan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
The issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023 concerning Instructions for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs has caused pros and cons reactions in society, in essence in this SEMA applications for registration of marriages between different religions cannot be granted by the Court, this is of course contrary to Supreme Court Decision Number 1400 K/Pdt/1986 which states that differences in the religion of prospective husband and wife are not prohibited in marriage, and also contradicts the content in the Elucidation of Article 35 letter a of Law Number 23, 2006 concerning Population Administration, where it is explained that the Court can determine marriages between people of different religions. This research aims to determine the position and legal strength of SEMA in the hierarchical system of statutory regulations. This research method uses normative juridical with a statutory approach. The research results show that the position of SEMA Number 2 of 2023 is under the law and its legal force cannot erase or revoke articles in the Population Administration law, even though SEMA Number 2 of 2023 contains the same material as Article 2 paragraph (1 ) and Article 8 letter f of Law Number 1 of 1974 concerning Marriage, but can only revoke legal products issued by the Supreme Court, so with the issuance of SEMA this automatically revokes Supreme Court Decision Number 1400 K/Pdt/1986. The binding legal power of SEMA is not directly legally binding, but contains legal relevance aimed at the Judicial body under the Supreme Court, thus closing the door for the Court to grant Applications for Registration of Interfaith marriage.